Trastornos disocial y el comportamiento escolar en los estudiantes de la Unidad Educativa Nicolás Infante Díaz, año 2019 - Toapanta Oña, Eva Maclovia (2019)
The purpose of this study on problems of disocial disorders and its impact on school behavior that is established in the nineteenth century. These are students with isolation behavior violate the fundamental rights of others have problems of aggression towards their peers, parents and teachers, with uncontrolled tantrums, robberies, lies, complaints from teachers, for the constant tantrums, disobedience and negativism Of the students these are the most frequent behavior problems that occur in schools nationwide. Most of the disocial behaviors shown by adolescents can be explained as a mismatch within their family, school or social context, but if it remains in time, students present it can be indicated by teachers and peers as problematic with the consequent label that, in addition, is usually accompanied by other situations that hinder the possibilities of adaptation and normalization of its development including social skills, that is, they are difficult to handle conflicts and solve problems. Behavioral problems occur, at very early stages of development, establishing complications in the school and family relationships, generating a destructive relationship with students. Behavioral problems, painfully, have increased, giving as their main characteristics their age of early onset as the means in which it develops as the genetic factor, and the education they have obtained during this time.